Poinsettias at a Glance - Sydney Park Brown (EDIS, 2008)
ENH-1083, a 2-page illustrated fact sheet by Sydney Park Brown, provides basic information for growing these decorative potted Christmas season plants — interesting facts, caring for them potted or as outdoor plants, and troubleshooting. Includes references. Published by the UF Department of Environmental Horticulture, December 2007.